Impact of four Glomus species on the growth, oil content, P content and phosphatase activity of Vetiveria zizanioides - and H.N VERMA, NEELIMA RATTI* S.P. GAUTAM (Indian Phytopathology, 2002)
Vetiveria zizanioides plants were inoculated with Glomus aggregatum, G. fasciculatum, G. mosseae and G. intraradices. All the four species enhanced biomass, P content of root and shoot tissue, acid and alkaline phosphatase activity of the roots as compared to control plants. Total dry weight (biomass) was 17.5% and 17.2% higher in G. mosscae and G. fasciculatum treatment respectively, than control. P content in stem was 81.3% (highest) and 60% higher in G. fasciculatum and G. mosseae treatments, respectively. Acid phosphatase activity was 168.5% higher in G. fasciculatum. Root colonization in G. fasciculatum was highest (88.3%). Among all the species G. fasciculatum and G. mosseae had more superior symbiotic relationship with vetiver plants. Although G. fasciculatum and G. mosseae increased biomass, P content and phosphatase activity of the plants, oil percent was maximum (1.67%) in control plants. The reason may be, that mycorrhizal plants produced more adventitious roots than non mycorrhizal plants and also maximum quantity of oil is extracted from main roots of the' plant. Oil percentage was 1.5% in G. fasciculatum treatment, where it was maximum among all other treatments. Major derivatives of the oil were almost similar in control as well as G. fasciculatum treatment in percentage.